Composite fiber winding interwoven high-performance lithium metal negative electrode and its preparation method and application

Through composite fiber wire winding and interwoven high-performance lithium metal negative electrode, the electrochemical instability and lack of subjectivity of lithium metal negative electrode is solved, and high Coulomb efficiency and long cycle stability are achieved, suitable for high energy density and long life lithium Metal battery.

CN118645583BActive Publication Date: 2025-01-14HARBIN INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410829391.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-25
Publication Date
2025-01-14
Estimated Expiration
2044-06-25

AI Technical Summary

Technical Problem

The lithium metal negative electrode causes dendrites to grow and expand in volume due to electrochemical instability and insubjectivity, which in turn accelerates the decomposition of electrolytes and corrosion of lithium metal, hinders its application in high-energy density and long-life batteries.

Method used

Compound fiber wire winding and interwoven high-performance lithium metal negative electrodes are used to form composite fiber wires through the winding of polymer main fiber wires and multifunctional fiber wires, induce uniform deposition of lithium ions, alleviate electrolyte decomposition and corrosion of lithium metal, and improve Coulomb efficiency and Cyclic stability.

Benefits of technology

It achieves high Coulomb efficiency and long cycle stability, reduces the desolvation energy of lithium ions, inhibits the growth of lithium dendrites, increases the conductivity and heat dissipation performance of lithium metal negative electrodes, alleviates the problem of volume expansion, and is suitable for extreme working environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118645583B_ABST
    Figure CN118645583B_ABST
Patent Text Reader

Abstract

The present invention discloses a composite fiber filament winding interweaving type high-performance lithium metal negative electrode and its preparation method and application, wherein the negative electrode comprises composite fiber filaments and active materials filled in the composite fiber filaments, wherein: the composite fiber filaments are formed by winding multifunctional fiber filaments and polymer main fiber filaments, the polymer main fiber filaments serve as the main skeleton, and the multifunctional fiber filaments are wound on the polymer main fiber filaments; the multifunctional fiber filaments comprise copper fiber filaments and a bipolar protective layer selectively coated on the surface of the copper fiber filaments, the bipolar protective layer is located on the upper surface of the composite fiber filaments as the winding progresses, and the copper fiber filaments are located on the lower surface of the composite fiber filaments. The present invention forms a composite fiber filament by winding and interweaving the polymer main fiber filaments and the multifunctional fiber filaments as the "host" skeleton of lithium metal, inducing rapid and uniform deposition of lithium ions, alleviating the continuous decomposition of the electrolyte and the consumption of active lithium, achieving high coulomb efficiency while minimizing corrosion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium batteries and relates to a lithium metal negative electrode, and specifically relates to a composite fiber filament wound interwoven high-performance lithium metal negative electrode and a preparation method and application thereof. Background Art

[0002] At present, the energy density of lithium-ion batteries based on intercalation chemistry is about 250-300 Wh kg -1 However, with the development of electric vehicles, electric aircraft and special equipment for extreme environments, there is an urgent need to develop higher energy density (500Whkg -1 ), long-life rechargeable batteries. Lithium metal anode has a high theoretical specific capacity (3860mAh g -1 ) and low operating voltage (-3.04V compared to the standard hydrogen electrode), it is considered to be one of the most promising negative electrode materials for the next generation of energy storage systems. However, the electrochemical instability and hostlessness of lithium metal anodes cause them to suffer from uncontrollable dendrite growth and volume expansion problems during the deposition / dissolution process, thereby accelerating the continuous decomposition of the electrolyte and the corrosion of lithium metal, resulting in lower Coulombic efficiency and poor cycle stability, which in turn hinders the practical application of lithium metal anodes.

[0003] To solve the above problems, researchers are committed to developing new electrolyte systems and additives, constructing a stable artificial interface layer to regulate the reactivity of the lithium metal anode and electrolyte and improve the stability of the interface. Different from the single design of the lithium metal interface, the use of a multifunctional composite "host" can provide an anti-corrosion protection layer, improve the coulombic efficiency and slow down the loss of electrochemically active lithium. On the other hand, it allows for uniform and rapid transmission of lithium ions, accelerates desolvation kinetics, alleviates the phenomenon of local supersaturation of lithium ion concentration, and inhibits the growth of lithium dendrites. At the same time, it has a certain volume adaptive ability, which can alleviate the volume change caused by the deposition / dissolution process of lithium metal, making it an efficient method to improve the long-cycle stability of lithium metal batteries in extreme working environments. Summary of the invention

[0004] In order to solve the problems of low coulombic efficiency and poor cycle stability of lithium metal batteries in practical applications, the present invention provides a composite fiber filament winding interwoven high-performance lithium metal negative electrode and its preparation method and application. The present invention forms a composite fiber filament by winding a polymer main fiber filament and a multifunctional fiber filament as a "host" skeleton of lithium metal, inducing rapid and uniform deposition of lithium ions, alleviating the continuous decomposition of electrolytes and the consumption of active lithium, achieving high coulombic efficiency while minimizing corrosion.

[0005] The objective of the present invention is achieved through the following technical solutions:

[0006] A composite fiber filament winding and interweaving type high-performance lithium metal negative electrode, comprising composite fiber filaments and active materials filled in the composite fiber filaments, wherein:

[0007] The composite fiber filaments are formed by winding the multifunctional fiber filaments and the polymer main fiber filaments, the polymer main fiber filaments serve as the main skeleton, and the multifunctional fiber filaments are wound around the polymer main fiber filaments;

[0008] The multifunctional fiber yarn comprises a copper fiber yarn and a bipolar protective layer selectively coated on the surface of the copper fiber yarn. The bipolar protective layer is located on the upper surface of the composite fiber yarn as it is wound, and the copper fiber yarn is located on the lower surface of the composite fiber yarn.

[0009] A method for preparing the composite fiber filament wound interwoven high-performance lithium metal negative electrode comprises the following steps:

[0010] Step 1: Preparation of polymer main fiber:

[0011] Step 11, preparation of electrospinning solution: weigh a certain amount of polymer monomer material 1 in a solvent, heat and stir at a temperature of 40 to 60° C. for 5 to 12 hours, add the conductive polymer material 2 to the above solution, heat and stir the mixed solution at a temperature of 50 to 70° C. for 4 to 10 hours, add an initiator to the above mixed solution, heat at a temperature of 45 to 70° C. for 18 to 26 hours until the reaction is completed, and form a colorless and transparent electrospinning solution, wherein:

[0012] The solvent is one of dimethylformamide, ethyl acetate, ether, and cyclohexanone; the polymer monomer material 1 includes one of acrylonitrile, vinyl pyrrolidone, methyl methacrylate, methacrylic acid, and N'N-methylenebisacrylamide; the conductive polymer material 2 includes one of conductive polymers such as poly[(trimethoxysilyl)propyl]aniline, polypyrrole, polyethylene-(3,4-dioxythiophene), polystyrene sulfonic acid, polythiophene, and polyaniline; and the initiator is persulfate;

[0013] In the electrospinning solution, the mass fraction of the polymer monomer material 1 is 15-40wt%, the mass ratio of the polymer monomer material 1 to the polymer material 2 is 1:1-3, and the mass of the initiator accounts for 0.1-0.3wt% of the total mass of the electrospinning solution;

[0014] Step 1 and 2, preparation of polymer fiber: under the conditions of temperature of 20-60°C and humidity of 50%, add the above electrospinning solution into a disposable syringe and fix it on the device for electrospinning, control the electrospinning voltage to 13-17 kV, the receiving distance to 12-16 cm, and the feeding speed to 5-8 μL min -1 , adjust the rotation speed of the drum to 200~240rpm min-1 ; The obtained electrospun fibers are placed in a vacuum drying oven at 60-120° C. and dried for 16-24 hours to obtain polymer main fibers;

[0015] In this step, the ratio of polymer monomer material 1 and conductive polymer material 2 is controlled, and a main fiber with a layered structure is prepared by an electrospinning method. The conductive polymer is wrapped around the outside of the main fiber, so that it has both excellent mechanical properties and conductivity.

[0016] Step 2: Preparation of multifunctional fiber:

[0017] Step 21. Preparation of coating mixture: Add a certain amount of solvent and precursor material A to a container equipped with a magnetic stirring bar, ultrasonically disperse for 10 to 30 minutes, add monomer material B containing a sulfonic acid group or a nitrile group structure, and then add a certain amount of initiator, stir at 60 to 85° C. for 10 to 18 hours to obtain a mixture that can be coated on the surface of the metal fiber, wherein:

[0018] The solvent includes one of deionized water, ethanol, ethylene glycol, acetone, N,N-dimethylformamide, etc., the precursor material A includes one of 2-hydroxyethyl acrylate, ethylene glycol diacrylate, vinyl alcohol, ethylene glycol, and polyimide (small molecule), the monomer material B containing a sulfonic acid group or a nitrile group structure includes one of sodium p-styrene sulfonate, sulfonated styrene, vinyl sulfonic acid, sulfonated aniline, sulfonated benzimidazole, and cyanoethylated polyvinyl alcohol, and the initiator includes one of ammonium persulfate, potassium persulfate, 2-hydroxy-2-methyl-1-phenyl-1-propanone, dibenzoyl peroxide, di-tert-butyl peroxide, and azobisisobutyronitrile;

[0019] In the mixture, the mass fraction of the precursor material A is 20-35wt%, the mass ratio of the precursor material A to the monomer material B is 1:1-4, and the mass of the initiator accounts for 0.1-0.5wt% of the total mass of the mixture;

[0020] Step 22, preparation of functional fiber filaments: The mixture prepared in step 21 is selectively coated on the surface of the copper fiber filament by a certain method, and the coating interval is set to 0.1-0.6 mm, and then the coated multifunctional fiber filament is heated under vacuum conditions at a temperature of 60-80° C. for 4-7 hours, wherein:

[0021] The selective coating method may be one of a template coating method, an inkjet printing method, a direct coating method, and a masking film coating method;

[0022] The purpose of this step is to obtain a more dense and uniform continuous structure of the multifunctional coating layer-copper layer. The precursor material A can be combined with the copper substrate through hydrogen bonding to avoid the separation of the copper substrate and the coating layer during use. The highly stable polymer protective layer can prevent further reaction of the electrolyte and improve the corrosion resistance of the lithium metal negative electrode. The monomer material B containing a sulfonic acid group or a nitrile group structure can induce the uniform deposition of lithium ions at the interface through ion-dipole interaction, inhibit the growth of lithium dendrites, and improve the overall performance of the battery.

[0023] Step 3: preparing a current collector by winding and interweaving the composite fiber filaments:

[0024] The polymer main fiber filament obtained in step 1 is used as the main skeleton, and the multifunctional fiber filament obtained in step 2 is wound on the polymer main fiber filament to obtain a composite fiber filament, and the composite fiber filament is interlaced with each other by a braiding machine in the form of warp and weft to obtain a current collector based on the winding and interweaving of the composite fiber filament;

[0025] The purpose of this step is to give full play to the role of the multifunctional coating layer and the copper layer through the winding method, wherein the functional coating layer is located on the top of the current collector, and the copper layer is located at the bottom of the current collector. The polymer in the multifunctional coating layer contains soft segments and high ionic conductivity segments, which can improve the flexibility and ion transport of the local interface. The copper layer can increase the conductivity and heat dissipation performance of the lithium metal negative electrode and reduce the internal resistance of the battery. The overall structure of the composite fiber filaments interwoven by the warp and weft can provide sufficient volume adaptability to alleviate the volume expansion of lithium metal during the deposition / dissolution process.

[0026] Step 4: Preparation of composite fiber winding and interweaving type high-performance lithium metal negative electrode:

[0027] The current collector obtained in step three is filled with lithium metal active materials by methods such as electrochemical lithium plating, physical lithium pressing, and molten lithium loading to prepare a composite fiber-wound interwoven high-performance lithium metal negative electrode.

[0028] The above-mentioned composite fiber filament wound and interwoven high-performance lithium metal negative electrode can be used in lithium metal batteries. The lithium metal battery can be a soft-pack battery, a square aluminum shell battery or a button battery assembled with the above-mentioned composite fiber filament wound and interwoven lithium metal negative electrode sheets. The top of the prepared composite lithium metal negative electrode is placed facing the diaphragm, and an appropriate amount of electrolyte is injected. The positive electrode uses a high-nickel active material, and the battery is packaged to obtain a high-energy density lithium metal battery.

[0029] Compared with the prior art, the present invention has the following advantages:

[0030] (1) The present invention innovatively combines the joint design strategy of interface chemistry and structural engineering, adopts the method of winding fiber filaments to realize the preparation of multifunctional interwoven host materials, and forms a composite negative electrode by filling lithium metal particles, which is crucial for achieving long-term cycle stability of lithium metal batteries and extending their calendar life, especially under extreme working environments.

[0031] (2) The heterostructure formed by winding of the present invention is conducive to meeting the needs of lithium metal batteries in the long-term cycle process. The design of the top bipolar layer can not only reduce the desolvation energy of lithium ions, reduce the local current density, and guide the uniform deposition of lithium ions, but also change the adsorption orientation of the electrolyte components, thereby alleviating the continuous consumption of the electrolyte and the corrosion of lithium metal to the greatest extent; the design of the bottom copper layer can increase the conductivity and heat dissipation capacity of the lithium metal negative electrode and reduce the internal resistance of the battery.

[0032] (3) The overall framework structure formed by the intertwining of fiber filaments has excellent volume adaptability and can effectively alleviate problems such as volume expansion caused by the deposition / dissolution of lithium metal.

[0033] (4) The composite fiber-wrapped interwoven current collector of the present invention is highly compatible with the soft-pack battery process and is easy to mass-produce, which is conducive to promoting the application of high-energy-density lithium metal batteries under extreme working conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a flow chart for the preparation of composite fiber-wound interwoven lithium metal negative electrode.

[0035] Figure 2 It is a schematic diagram of the structure of a composite fiber-wrapped interwoven lithium metal negative electrode.

[0036] Figure 3 This is a SEM image of the composite fiber obtained by winding.

[0037] Figure 4 The symmetrical battery assembled according to Example 1 and Comparative Example 1 was subjected to a current density of 2 mA cm -2 , the deposition surface capacity is 2 mAh cm -2 Comparison of long cycle performance under different conditions.

[0038] Figure 5 These are SEM images of the symmetrical batteries assembled according to Example 1 and Comparative Example 1 after cycling, (a) Example 1, (b) Comparative Example 1.

[0039] Figure 6 It is a comparison chart of the full battery cycle performance of Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0040] The technical solution of the present invention is further described below in conjunction with the embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.

[0041] Example 1

[0042] Step 1: Preparation of polymer main fiber:

[0043] A certain amount of methyl methacrylate was weighed into dimethylformamide at a mass fraction of 25wt%, and heated and stirred at 60°C for 10h. Polyethylene-(3,4-dioxythiophene) was added to the above solution at a mass ratio of 1:2. The mixed solution was heated and stirred at 60°C for 6h. An initiator, persulfate, was added, and the mass of the initiator accounted for 0.1wt% of the total mass. The mixture was heated at 70°C for 24h until the reaction was completed and a colorless and transparent electrospinning solution was formed for later use.

[0044] Step 1: Preparation of polymer main fiber:

[0045] Step 11, preparation of electrospinning solution: weigh a certain amount of methyl methacrylate and dissolve it in dimethylformamide, heat and stir for 10 hours at 60°C, add polyethylene-(3,4-dioxythiophene) to the above solution, heat and stir the mixed solution at 60°C for 6 hours, add persulfate to the above mixed solution, heat at 70°C for 24 hours until the reaction is completed to form a colorless and transparent electrospinning solution for standby use, wherein: in the electrospinning solution, the mass fraction of methyl methacrylate is 25wt%, the mass ratio of methyl methacrylate to polyethylene-(3,4-dioxythiophene) is 1:2, and the mass of persulfate accounts for 0.1wt% of the total mass of the electrospinning solution.

[0046] Step 1 and 2: Preparation of polymer fiber: Under the conditions of temperature of 30°C and humidity of 50%, add the above electrospinning solution into a disposable syringe and fix it on the device for electrospinning. The voltage of electrospinning is controlled to be 15 kV, the receiving distance is 15 cm, and the feeding speed is 6 μL min -1 , adjust the rotation speed of the drum to 230 rpm min -1 The electrospun fibers were placed in a vacuum drying oven at 100°C for 24 hours to obtain polymer main fibers. The ratio of methyl methacrylate and polyethylene-(3,4-dioxythiophene) was controlled, and the main fibers with a layered structure were prepared by electrospinning. Polyethylene-(3,4-dioxythiophene) was wrapped around the outside of methyl methacrylate, making it have both excellent mechanical properties and conductivity.

[0047] Step 2: Preparation of multifunctional fiber:

[0048] Step 21. Preparation of a coating mixture: Add a certain amount of ethylene glycol and 2-hydroxyethyl acrylate to a container equipped with a magnetic stirring bar, ultrasonically disperse for 30 minutes, add sodium p-styrene sulfonate, and then add a certain amount of ammonium persulfate, stir at 75°C for 15 hours to obtain a mixture that can be coated on the surface of the metal fiber wire, wherein: in the mixture, the mass fraction of 2-hydroxyethyl acrylate is 23wt%, the mass ratio of 2-hydroxyethyl acrylate to sodium p-styrene sulfonate is 1:1, and the mass of ammonium persulfate accounts for 0.3wt% of the total mass of the mixture.

[0049] Step 22, preparation of functional fiber filaments: The mixture prepared in step 21 is selectively coated on the surface of the copper fiber filament by inkjet printing, the mixture is poured into an ultrasonic coating machine, the coating spacing is set to 0.5mm, and then the coated multifunctional fiber filament is heated under vacuum conditions at a temperature of 80°C for 6h to obtain a more dense and uniform multifunctional fiber filament, showing a continuous structure of the coating layer-copper layer. The soft polymer segment of poly 2-hydroxyethyl acrylate can be combined with the copper substrate through hydrogen bonding to avoid the separation of the copper substrate and the coating layer during use. The highly stable polymer protective layer can prevent further reaction of the electrolyte and improve the corrosion resistance of the lithium metal negative electrode. The sulfonate group in poly (sodium p-styrene sulfonate) promotes the migration of lithium ions at the interface through ion-dipole interaction, induces uniform deposition of lithium ions at the interface, inhibits the growth of lithium dendrites, and improves the comprehensive performance of the battery under extreme environmental conditions (low temperature / high current density).

[0050] Step 3: preparing a current collector by winding and interweaving the composite fiber filaments:

[0051] The polymer main fiber obtained in step 1 is used as the main skeleton, and the multifunctional fiber obtained in step 2 is wound on the polymer main fiber to obtain a composite fiber. The composite fiber is interlaced with warp and weft by a braiding machine to obtain a current collector based on the interlacing of the composite fiber. Figure 3 ).

[0052] Step 4: Preparation of composite lithium metal anode and assembly of lithium metal battery:

[0053] Step 41. Preparation of a composite lithium metal negative electrode: Fill the intertwined current collector obtained in step 3 with active materials by a molten lithium loading method, place the intertwined current collector on top of the molten lithium, and prepare a composite lithium metal negative electrode after the molten lithium is infiltrated.

[0054] Step 42. Assembly of lithium metal batteries: The lithium metal battery can be a symmetrical battery or a full battery assembled with the lithium metal negative electrode sheets wound and interwoven with the above-mentioned composite fiber filaments. The top of the prepared composite lithium metal negative electrode is facing the diaphragm, and an appropriate amount of electrolyte is injected. The positive electrode material is a high-nickel active material / composite lithium metal negative electrode, and the battery is packaged to obtain a high-energy density lithium metal battery.

[0055] The performance of the assembled symmetrical battery at low temperature is as follows Figure 4 As shown in Figure 2, for the unmodified lithium metal anode, the symmetric battery has a smaller overpotential, indicating that the composite lithium metal anode can effectively regulate the reaction kinetics of lithium ions and effectively reduce the potential polarization phenomenon during lithium deposition. Figure 5 The SEM image shows that the composite lithium metal anode can also induce uniform lithium deposition and inhibit the growth of lithium dendrites. The assembled full battery has excellent cycle stability at low temperature. Figure 6 shown.

[0056] Example 2

[0057] The present embodiment is different from the embodiment 1 in that the polymer monomer material 1 in step 1 is changed to acrylonitrile, which can achieve the same effect.

[0058] Example 3

[0059] The difference between this embodiment and embodiment 1 is that the conductive polymer monomer material 2 in step 1 is changed to poly[(trimethoxysilyl)propyl]aniline, which can achieve the same effect.

[0060] Example 4

[0061] The difference between this embodiment and embodiment 1 is that the monomer material B in step 2 is changed to cyanoethylated polyvinyl alcohol, which can achieve the same effect.

[0062] Example 5

[0063] The difference between this embodiment and embodiment 1 is that the selective coating method in step 2 is changed to a template coating method, which can achieve the same effect.

[0064] Example 6

[0065] The difference between this embodiment and embodiment 1 is that the method of filling the active material in the intertwined current collector in step 4 is physical lithium pressing, that is, by pressing the prepared intertwined current collector on lithium foil through a simple physical pressing method, a composite lithium metal negative electrode can be prepared, which can achieve the same effect.

[0066] Comparative Example 1

[0067] The difference between this comparative example and Example 1 is that the negative electrode used is a lithium metal sheet that has not been treated in any way, and the battery is assembled in no fixed direction.

[0068] Comparative Example 2

[0069] The difference between this comparative example and Example 1 is that the lithium metal surface is only treated by a polymer coating of poly(sodium p-styrene sulfonate). The purpose of this step is to improve the deposition uniformity of lithium ions on the interface only by surface treatment, without any special structural setting.

Claims

1. A composite fiber-wound interwoven high-performance lithium metal negative electrode, characterized in that The negative electrode comprises composite fiber filaments and active materials filled in the composite fiber filaments, wherein: The composite fiber filaments are formed by winding the multifunctional fiber filaments and the polymer main fiber filaments, the polymer main fiber filaments serve as the main skeleton, and the multifunctional fiber filaments are wound around the polymer main fiber filaments; The multifunctional fiber filaments include copper fiber filaments and a bipolar protective layer selectively coated on the surface of the copper fiber filaments, the bipolar protective layer is located on the upper surface of the composite fiber filaments as it is wound, and the copper fiber filaments are located on the lower surface of the composite fiber filaments; The preparation steps of the multifunctional fiber are as follows: Step (1), preparation of a coating mixture: adding a certain amount of solvent and precursor material A to a container equipped with a magnetic stirring bar, ultrasonically dispersing for 10 to 30 minutes, adding a monomer material B containing a sulfonic acid group or a nitrile group structure, and then adding a certain amount of initiator, stirring at 60 to 85° C. for 10 to 18 hours to obtain a mixture that can be coated on the surface of the metal fiber wire, wherein: in the mixture, the mass fraction of the precursor material A is 20 to 35wt%, the mass ratio of the precursor material A to the monomer material B is 1:1 to 4, and the mass of the initiator accounts for 0.1 to 0.5wt% of the total mass of the mixture; the precursor material A comprises one of 2-hydroxyethyl acrylate, ethylene glycol diacrylate, vinyl alcohol, ethylene glycol, and polyimide; Step (2), preparation of functional fiber filaments: the mixture prepared in step (1) is selectively coated on the surface of the copper fiber filaments by a certain method, and then the coated multifunctional fiber filaments are heated under vacuum conditions at a temperature of 60 to 80° C. for 4 to 7 hours.

2. A method for preparing a high-performance lithium metal negative electrode of a composite fiber winding interwoven type as claimed in claim 1, characterized in that The method comprises the following steps: Step 1: Preparation of polymer main fiber: Step 11, preparation of electrospinning solution: weigh a certain amount of polymer monomer material 1 in a solvent, heat and stir for 5 to 12 hours at a temperature of 40 to 60° C., add conductive polymer material 2 to the polymer monomer material 1 solution, heat and stir the mixed solution at a temperature of 50 to 70° C. for 4 to 10 hours, add an initiator to the mixed solution after heating and stirring, and heat at a temperature of 45 to 70° C. for 18 to 26 hours until the reaction is completed to form a colorless and transparent electrospinning solution, wherein: in the electrospinning solution, the mass fraction of the polymer monomer material 1 is 15 to 40wt%, the mass ratio of the polymer monomer material 1 to the polymer material 2 is 1:1 to 3, and the mass of the initiator accounts for 0.1 to 0.3wt% of the total mass of the electrospinning solution; Step 1 and 2, preparation of polymer fiber filaments: under the conditions of temperature of 20-60°C and humidity of 50%, the electrospinning solution is added into a disposable syringe and fixed on a device for electrostatic spinning, and the obtained electrospun fiber is placed in a vacuum drying oven at 60-120°C and dried for 16-24h to obtain polymer main fiber filaments; Step 2: Preparation of multifunctional fiber: Step 21. Preparation of a coating mixture: Add a certain amount of solvent and precursor material A to a container equipped with a magnetic stirring bar, ultrasonically disperse for 10 to 30 minutes, add a monomer material B containing a sulfonic acid group or a nitrile group structure, and then add a certain amount of initiator, stir at 60 to 85°C for 10 to 18 hours to obtain a mixture that can be coated on the surface of the metal fiber wire, wherein: in the mixture, the mass fraction of the precursor material A is 20 to 35wt%, the mass ratio of the precursor material A to the monomer material B is 1:1 to 4, and the mass of the initiator accounts for 0.1 to 0.5wt% of the total mass of the mixture; the precursor material A includes one of 2-hydroxyethyl acrylate, ethylene glycol diacrylate, vinyl alcohol, ethylene glycol, and polyimide; Step 22, preparation of functional fiber filaments: selectively coating the mixture prepared in step 21 on the surface of the copper fiber filaments by a certain method, and then heating the coated multifunctional fiber filaments under vacuum conditions at a temperature of 60 to 80° C. for 4 to 7 hours; Step 3: preparing a current collector by winding and interweaving the composite fiber filaments: The polymer main fiber filament obtained in step 1 is used as the main skeleton, and the multifunctional fiber filament obtained in step 2 is wound on the polymer main fiber filament to obtain a composite fiber filament, and the composite fiber filament is interlaced with each other by a braiding machine in the form of warp and weft to obtain a current collector based on the interweaving of the composite fiber filament; Step 4: Preparation of composite fiber-wound high-performance lithium metal anode: The current collector obtained in step three is filled with lithium metal active materials to prepare a composite fiber filament wound and interwoven high-performance lithium metal negative electrode.

3. The method for preparing a composite fiber filament wound interwoven high-performance lithium metal negative electrode according to claim 2, characterized in that In the step 11, the solvent is one of dimethylformamide, ethyl acetate, ether, and cyclohexanone, the polymer monomer material 1 includes one of acrylonitrile, vinyl pyrrolidone, methyl methacrylate, methacrylic acid, and N'N-methylenebisacrylamide, the conductive polymer material 2 includes one of poly[(trimethoxysilyl)propyl]aniline, polypyrrole, polyethylene-(3,4-dioxythiophene), polystyrene sulfonic acid, polythiophene, and polyaniline, and the initiator is persulfate.

4. The method for preparing a composite fiber-wound interwoven high-performance lithium metal negative electrode according to claim 2, characterized in that In the steps 1 and 2, the voltage of the electrospinning was controlled to be 13-17 kV, the receiving distance was 12-16 cm, and the feeding speed was 5-8 μL min -1 , adjust the rotation speed of the drum to 200~240rpm min -1 .

5. The method for preparing a composite fiber filament wound interwoven high-performance lithium metal negative electrode according to claim 2, characterized in that In the step 21, the solvent includes one of deionized water, ethanol, ethylene glycol, acetone, and N,N-dimethylformamide; the monomer material B containing a sulfonic acid group or a nitrile group structure includes one of sodium p-styrene sulfonate, sulfonated styrene, ethylene sulfonic acid, sulfonated aniline, sulfonated benzimidazole, and cyanoethylated polyvinyl alcohol; and the initiator includes one of ammonium persulfate, potassium persulfate, 2-hydroxy-2-methyl-1-phenyl-1-propanone, dibenzoyl peroxide, di-tert-butyl peroxide, and azobisisobutyronitrile.

6. The method for preparing a composite fiber-wound interwoven high-performance lithium metal negative electrode according to claim 2, characterized in that In the step 22, the selective coating interval is set to 0.1-0.6 mm.

7. The method for preparing a composite fiber-wound interwoven high-performance lithium metal negative electrode according to claim 2, characterized in that In the step 22, the selective coating method is one of a template coating method, an inkjet printing method, a direct coating method and a masking film coating method.

8. The method for preparing a composite fiber-wound interwoven high-performance lithium metal negative electrode according to claim 2, characterized in that In step 4, the method of filling the active material is one of the following methods: electrochemical lithium plating, physical lithium pressing, and molten lithium loading.

9. Use of the composite fiber filament wound and interwoven high-performance lithium metal negative electrode according to claim 1 in a lithium metal battery.

10. The use of the composite fiber-wound interwoven high-performance lithium metal negative electrode in a lithium metal battery according to claim 9, characterized in that The lithium metal battery is a soft-pack battery, a square aluminum shell battery or a button battery assembled with a composite fiber-wound interwoven lithium metal negative electrode sheet.

Citation Information

Patent Citations

  • Composite lithium metal anode

    CN108281612A

  • Self-supporting lithium metal negative electrode material and preparation method and application thereof

    CN112054203A